Sosialisasi Meningkatkan Kesadaran Generasi Muda Tentang Memahami Penghasilan Tidak Kena Pajak Bagi Siswa SMK Negeri 1 Pasaman Barat - Firta, Widia; Putra, Dike Rama; Pratama, Rahmatullah (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service is an activity of the Indonesian Men's University "YPTK" Padang lecturer team to carry out outreach to increase awareness of the younger generation about understanding non-taxable income for students at SMK Negeri 1 Pasaman Barat. The activities provided aim to make the younger generation aware of the importance of reporting taxes even though they don't have any income. This activity was carried out as feedback from the needs analysis action (need survey) which had been carried out by the service team for the younger generation, where information was obtained that many young people did not understand the limit of income that was not subject to tax for individual taxpayers according to the amount his family's responsibilities. The service is carried out using 2 methods, namely direct lectures which contain explanations about taxes and the importance of tax reporting.